Mapeamento de fluxo de valor: aplicação em uma indústria de farinha de trigo - Schulz, Natália Peres (2018)
As Brazil is going through a crisis that affects a great majority of industries, all waste avoided by the company has a very important meaning. For the wheat flour industry is no different, forcing as companies to reinvent themselves and use process improvement methods. The objective of this work is to analyze and identify problems in a wheat flour industry, from a production engineering tool, to propose solutions and solutions for a company. By means of tools, it was possible to verify some problems and wastes, and as proposals for improvements presented here, we reached the result of a decrease in delivery time by 7.47% and increase the production capacity of the line by 14.17%. which is an extremely significant value.